(untitled) (Global Journal of Management and Business Research, 2014)
This study is aimed to determine the impact of the financial resources available to the Development Bank of City and villages on size of credit facilities granted for the period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012). Which represented in the financial resource available by both customer deposits, secretariats of the local Committees, loans and capital on volume of credit facilities by using unit root test to identify the stability of the data in the time series, and test the method of least squares regression analysis (OLS) to test the hypotheses. The results indicated no statistically significant impact for each of Capital and its equivalents, the volume of loans, and the secretariats of the local Committees on the average size of credit facilities. While showing a statistically significant impact on the size of customer’s deposits on the average credit facilities for the development bank of cities and villages. The study recommended that the Development Bank of cities and villages has to issue bonds with expanding the size of investment projects, also to increase the return through using of short-term investment projects with a higher return.